Evaluation of the Effectiveness of Tenofovir in Chronic Hepatitis B Patients - Ecin, Seval Müzeyyen; Çalık Başaran, Nursel; Aladağ, Murat (Acta Medica, 2020)
Introductıon: HBV infection is a global public health problem. Tenofovir disoproxil fumarate (TDF) and tenofovir alafenamide (TAF) are nucleotide reverse transcriptase inhibitors (NRTIs) that are used for the treatment of CHB infection. The aim of this study was to evaluate the treatment response and efficacy of TDF, which was a new treatment regimen in Turkey Materials and Methods: This descriptive, retrospective study was conducted between January 2009 and January 2011 at Inonu University Faculty, Turgut Ozal Medicine Center, Department of Internal Medicine, Division of Hepatology Outpatient Clinic. We included hepatitis B positive patients who started to use Tenofovir (TDF). We retrospectively reviewed the electronic medical files of Hepatitis B patients. HBsAg, Hepatit B surface antibody (Anti-HBsAb), HBeAg, Hepatit B e antibody (Anti-HBeAb), HBV-DNA, aspartate aminotransferase (AST), alanine aminotransferase (ALT) values were evaluated in the 1, 3., 6., 9., and 12. months. Result: None of the patients under TDF treatment were “primary resistant”. ALT normalization at 12th month was seen in 80.4% of study population. HBsAg seroconversion were detected only in one patient (0.85%) at 9 months and HBeAg seroconversion were observed in 9 (8.3%) under TDF treatment. At the sixth month of TDF treatment, complete response were found in 77 (65.8%), partial response in 21 (18%) and inadequate response were in 19 (16.2%). Among HBeAg positive patients, 44 (80 %) patients had undetectable HBV DNA levels at the end of 12th month and among HBeAg negative patients, 52 (91.2%) patients had undetectable HBV DNA levels at the end of 12th month (p<0.01). Discussion and Conclusion: among patients with chronic HBV infection, Tenofovir had satisfying antiviral efficacy. There is no primary resistance in patients treated with Tenofovir. Patients had statistically significant improvement in AST, ALT, HBV DNA levels